Spy Sinker - Deighton, Len, 1929- (United Kingdom : Hutchinson, 1990)
Spy Sinker starts in 1977 and ends in 1987. It tells the entire story in the previous five novels from the third person perspective (Bernard Samson's bosses, his colleagues, his girlfriend Gloria, and most of all his wife Fiona). Thus, it fills in the gaps in the story, as the previous five books only reveals what Bernard can see and think he understands. It also tells the back story leading up to the story in the five novels, which has only been hinted at previously.
MU
Escuela de Aviación y Logística.
Keywords: Novela inglesa; Literatura